2011
DOI: 10.1681/asn.2010121224
|View full text |Cite
|
Sign up to set email alerts
|

FGF-23 Associates with Death, Cardiovascular Events, and Initiation of Chronic Dialysis

Abstract: Concentrations of the phosphate-regulating hormone fibroblast growth factor-23 (FGF-23) are elevated in patients with chronic kidney disease (CKD), but whether higher plasma FGF-23 concentrations associate with all-cause mortality, cardiovascular events, or initiation of chronic dialysis is not completely understood. Here, we measured FGF-23 concentration in stored plasma samples from 1099 patients with advanced CKD who participated in The Homocysteine in Kidney and End Stage Renal Disease study. Mean serum ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
331
7
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(376 citation statements)
references
References 40 publications
21
331
7
10
Order By: Relevance
“…Nasrallah et al [13], found that Fibroblast growth factor-23 (FGF-23) is independently correlated to aortic calcification in haemodialysis patients. A reasonable explanation for this phenomenon is that FGF-23 may cause thickening and fibrosis of the carotid intima by binding to its receptor [14]. It is widely accepted that FGFR1 and FGFR4 are receptors for FGF-23, which are present in myocardial cells and the vascular membrane of the coronary vessels and veins.…”
Section: Discussionmentioning
confidence: 99%
“…Nasrallah et al [13], found that Fibroblast growth factor-23 (FGF-23) is independently correlated to aortic calcification in haemodialysis patients. A reasonable explanation for this phenomenon is that FGF-23 may cause thickening and fibrosis of the carotid intima by binding to its receptor [14]. It is widely accepted that FGFR1 and FGFR4 are receptors for FGF-23, which are present in myocardial cells and the vascular membrane of the coronary vessels and veins.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Several cohort studies have examined the relationship between FGF-23 and renal outcomes. [10][11][12][13][14][15] In line with findings in the Chronic Renal Insufficiency Cohort cohort 11 and in the MMKD study 10 from analyses not considering the FGF-23-ADMA interaction, we confirmed that the FGF-23-CKD progression relationship was independent of (1) classic risk factors and (2) CKD-specific risk factors, such as proteinuria and the GFR, that are known to belong to the strongest predictors of CKD progression, as well as (3) major biomarkers of CKD mineral and bone disorder, including serum phosphate, 1,25(OH) 2 D, and PTH. These results further highlight the potential relevance of FGF-23 as a novel risk factor for evolution toward kidney failure in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…in the United States, [11][12][13][14] as well as a large study in transplant recipients in Hungary, 15 have coherently associated high plasma FGF-23 with CKD progression toward kidney failure.…”
mentioning
confidence: 92%
“…A promising CKD biomarker is fibroblast growth factor 23 (FGF-23), which is highly increased in CKD patients and associated with cardiovascular disease and mortality (380)(381)(382). Other potentially interesting molecules include the tubular injury markers NGAL (383-385), KIM-1 (385-388), TIMP-2 (389), IGFBP7 (389) and liver-type fatty acid-binding protein (L-FABP) (390,391).…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%